Method for express determination of medical radionuclides ⁹⁹ᵐTc, ⁶⁷Cu concentration using spectrometer based on Si planar detector - Deiev, O.S.; Kiprich, S.K.; Maslov, N.I.; Ovchinnik, V.D.; Shulika, M.Y.; Vasiliev, G.P.; Yalovenko, V.I. (Вопросы атомной науки и техники, 2017)
The method of express analysis provides the measurement of radiation spectra of medical radionuclides by a detection module based on an uncooled silicon planar detector and a "scintillator-silicon photosensor" type module. A spectrometric device for express analysis of radionuclide concentration has been developed and its prototyping has been carried out, confirming the operability of the device. The spectrometer analyzer is powered from the USB port of the PC (including a laptop) that provides the possibility of autonomous operation. Test measurements were carried out using the prototype of the spectrometer and X-ray sources, as well as spectral distributions of the radiation of real samples of ⁹⁹ᵐTc in a special container (glass ampoule). For a Si-PIN-detector with a thickness of 300 μm, the emission spectrum consists of a line of ⁹⁹ᵐTc with an energy of 140.5 keV and two peaks of the characteristic X-ray radiation (CXR) of technetium. The calculation in GEANT4 shows the matching of the ⁹⁹ᵐTc activities obtained from the registration of CXR and the main line. A measurement of the technetium concentration both by the 140.5 keV line and on the CXR radiation was proposed that significantly increases the speed of the data accumulation.